The Soybean Purple Acid Phosphatase GmPAP14 Predominantly Enhances External Phytate Utilization in Plants - Kong, Youbin; Li, Xihuan; Wang, Bing; Li, Wenlong; Du, Hui; Zhang, Caiying (Frontiers in Plant Science, 2018)
Induction and secretion of acid phosphatases (APases) is considered to be an important strategy for improving plant growth under conditions of low inorganic phosphate (Pi). Purple acid phosphatases (PAPs), are an important class of plant APases that could be secreted into the rhizosphere to utilise organic phosphorus (Po) for plant growth and development. To date, only a few members of the PAP family have been identified in soybean. In this paper, we identified a secreted PAP in soybean, GmPAP14, and investigated its role in utilising external phytate, the main form of organic phosphorus in the soil. An analysis of its expression and promoter showed that GmPAP14 was mainly expressed in the root and was strongly induced following Po treatment, during which its expression expanded from meristematic to maturation zones and root hairs. In vitro enzyme assays indicated that GmPAP14 had a relatively high phytase activity. Furthermore, GmPAP14 overexpression increased secreted acid phosphatase (APase) activities and phytase activities, leading to the improved use of external plant phytate, higher phosphorus content, and increased shoot weight. Thus, these results confirmed that GmPAP14 is an important gene induced in response to Po, and that it predominantly participates in utilising external Po to enhance plant growth and development.